An update on current and future treatment options for chondrosarcoma. Issue 9 (2nd September 2019) - MacDonald, Iona J; Lin, Chih-Yang; Kuo, Shu-Jui; Su, Chen-Ming; Tang, Chih-Hsin
ABSTRACT: Introduction : Human chondrosarcomas (CS; a malignant cartilage-forming bone tumor) respond poorly to chemotherapy and radiation treatment, resulting in high morbidity and mortality rates. Expanded treatment options are urgently needed. Areas covered : This article updates our 2014 review, in which we evaluated the CS treatments available at that time and potential treatment options under investigation. Since then, advances in research findings, particularly from Chinese herbal medicines, may be bringing us closer to more effective therapies for CS. In particular, promising findings have been reported from research targeting platelet-derived growth factor receptor. Expert opinion : Few treatment options exist for CS; chemotherapy is not even an option for unresectable disease, in which 5-year survival rates are just 2%. New information about the multitude of genes and signaling pathways that encourage CS growth, invasion and metastasis are clarifying how certain signaling pathways and plant-derived active compounds, especially molecularly-targeted therapies that inhibit the PDGF receptor, interfering with these biological processes. This review summarizes discoveries from the last 5 years and discusses how these findings are fueling ongoing work into effectively dealing with the disease process and improving the treatment of CS.